1979
DOI: 10.1128/jvi.31.3.668-676.1979
|View full text |Cite
|
Sign up to set email alerts
|

Viral genome RNA serves as messenger early in the infectious cycle of murine leukemia virus

Abstract: When NIH/3T3 mouse fibroblasts were infected with the Moloney strain of murine leukemia virus, part of the viral genome RNA molecules were detected in polyribosomes of the infected cells early in the infectious cycle. The binding appears to be specific, since we could demonstrate the release of viral RNA from polyribosomes with EDTA. Moreover, when infection occurred in the presence of cycloheximide, most viral RNA molecules were detected in the free cytoplasm. Size analysis on polyribosomal viral RNA molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Early studies of avian and murine retroviruses reported the detection of full-length viral genomes in polysome-containing pellets. 21,22,23 In support of our findings, a recent ribosome profiling study of HIV-1 infected cells revealed ribosome-protected RNA fragments in the gag coding region already at one hour after infection. 24 In other studies, protein expression could be detected in case of MLV-based vectors with primer binding site (PBS) mutations 25 and modified lentiviral vectors with structural rearrangements of the genome to enable direct translation, such as 5' IRES insertion, 26 Reporter viruses were produced by transfecting viral plasmids together with a plasmid encoding VSV-G env (pCMV-VSV-G, kindly provided by Bob Weinberg; Addgene #8454), and in case of the minimal lentiviral vectors, also with a plasmid encoding HIV-1 gag, pol, tat and rev (psPAX2, kindly provided by Didier Trono; Addgene #12260) or with the packaging plasmid pCD/NL-BH*deltavpu/RT-that lacks RT activity due to the D110E mutation in the catalytic site (kindly provided by Jakob Reiser; Addgene: #136985).…”
Section: Main Textsupporting
confidence: 89%
“…Early studies of avian and murine retroviruses reported the detection of full-length viral genomes in polysome-containing pellets. 21,22,23 In support of our findings, a recent ribosome profiling study of HIV-1 infected cells revealed ribosome-protected RNA fragments in the gag coding region already at one hour after infection. 24 In other studies, protein expression could be detected in case of MLV-based vectors with primer binding site (PBS) mutations 25 and modified lentiviral vectors with structural rearrangements of the genome to enable direct translation, such as 5' IRES insertion, 26 Reporter viruses were produced by transfecting viral plasmids together with a plasmid encoding VSV-G env (pCMV-VSV-G, kindly provided by Bob Weinberg; Addgene #8454), and in case of the minimal lentiviral vectors, also with a plasmid encoding HIV-1 gag, pol, tat and rev (psPAX2, kindly provided by Didier Trono; Addgene #12260) or with the packaging plasmid pCD/NL-BH*deltavpu/RT-that lacks RT activity due to the D110E mutation in the catalytic site (kindly provided by Jakob Reiser; Addgene: #136985).…”
Section: Main Textsupporting
confidence: 89%
“…In this study, we have confinned and extended an initial finding by Salzberg and co-workers (21,23) concerning the inhibitory effect of cycloheximide on murine retrovirus infection. This inhibitory effect was observed in all cases ofretrovirus infection we examined, which included other murine ecotropic viruses and feline RD114 and baboon M7 endogenous viruses.…”
Section: Discussionmentioning
confidence: 58%
“…Together with their observations that reverse transcription was not required for abrogation, these workers concluded that the RNA served some function other than as template for viral DNA synthesis. A suggested possibility was that this RNA served as early mRNA, a concept based on several other reports (10,30). We cannot explain why virions produced by cells treated with dactinomycin do not abrogate Fv-J restriction whereas N-Pac virions do.…”
Section: Discussionmentioning
confidence: 77%